Impacts of projected urban expansion and global warming on cooling energy demand over a semiarid region. (16th November 2017) - Tewari, Mukul; Salamanca, Francisco; Martilli, Alberto; Treinish, Lloyd; Mahalov, Alex
Abstract: Large impacts of global warming and urbanization on near‐surface air temperature increase and cooling energy demand are expected for the American Southwest region. The relative importance of these two features and their interactions are studied by means of a mesoscale model with a multilayer building energy model that allows accounting for the feedback between cooling energy consumption and air temperature for a typical summer period in Arizona. This approach allows to separate the impact of global warming from the one due to urbanization, on energy demand and air temperature. Under the highest greenhouse gas emissions scenario (RCP8.5), adverse effects on mean air temperature of global warming overwhelm those from the urbanization of new areas. In particular, the mean temperature increase for a summer period due to global warming and urban expansion in the Phoenix metropolitan area is 3.6 °C and in the Tucson metropolitan area, it is 3.1 °C. These result in an increase in the spatial density of the cooling energy demand (MW km −2 ) by 36.2 and 42.6% in the respective regions compared to present consumption. The citywide cooling energy demand (MW) on the other hand, is expected to increase up to a factor two (Phoenix) and three (Tucson), with ∼75% of this increase due to urban expansion, and ∼25% due to global warming. Abstract : (a) Diurnal cycle of observed total electricity demand across the Phoenix metropolitan area for all weekdays (i.e. each DXY curve represents a particular weekday) of the 15‐day summertime period in June 2012. (b) Same as in (a) but for 2‐m urban air temperature.